Potato Response to Drought Stress: Physiological and Growth Basis - Gervais, Taylor; Creelman, Alexa; Li, Xiu-Qing; Bizimungu, Benoit; De Koeyer, David; Dahal, Keshav (Frontiers in Plant Science, 2021)
Drought poses a major challenge to potato production worldwide. Climate change is predicted to further aggravate this challenge by intensifying potato crop exposure to increased drought severity and frequency. There is an ongoing effort to adapt our potato production systems through development of drought-tolerant cultivars that are appropriately engineered for the changing environment. Breeding of drought- tolerant cultivars can be approached through the identification of drought-related physiological and biochemical traits and their deployment in new potato cultivars. Thus, the main objective of this study was to develop a method to identify and characterize potato genotypes tolerant to drought and related key traits. To achieve this objective, first we studied 56 potato genotypes including 51 cultivars and 5 advanced breeding lines to assess drought tolerance in terms of tuber yield in the greenhouse experiment. Drought differentially reduced tuber yield in all genotypes. Based on their capacity to maintain percent tuber yield under drought relative to their well-watered controls, potato genotypes differed in their ability to tolerate drought. We then selected six genotypes, Bannock Russet, Nipigon, Onaway, Denali, Fundy and Russet Narkotah, with distinct yield responses to drought to further examine the physiological and biochemical traits governing drought tolerance. Drought-induced reduction in tuber yield was only 15-20% for Bannock Russet and Nipigon, 44-47% for Onaway and Denali, and 83-91% for Fundy and Russet Norkotah. The tolerant genotypes, Bannock Russet and Nipigon, exhibited about 2-3 fold increase in instantaneous water use efficiency (WUE) under drought as compared to their well- watered controls. This stimulation was about 1.8-2 fold for moderately tolerant genotypes, Onaway and Denali, and only 1.5 fold for sensitive genotypes Fundy and Russet Norkotah. The differential stimulation of instantaneous WUE of tolerant and moderately tolerant genotypes versus sensitive genotypes was accounted for by differential suppression of rates of photosynthesis, stomatal conductance and transpiration rates across genotypes. Potato genotypes varied in their response to leaf protein content under drought. We suggest that rates of photosynthesis, instantaneous WUE, and leaf protein content can be used as selection criteria for potato drought tolerance.